A functionally tunable magnetic nanochains platform for N-glycoproteomic analysis of extracellular vesicles from ultratrace biofluids - Mingyang Li; Xiaorong Song; Haixia Tu; Jie Sun; Yuanyuan Deng; Bing Wang; Yuhan Cai; Yulian Wang; Bin Li; Yue Wang; Xiangzheng Zhang; Dong Wei; et al. (Nature Communications)
Abstract Extracellular vesicles (EVs) carry complex glycoproteins critical mediators of disease progression and hold great potential for liquid biopsy applications. However, their low abundance presents significant analytical challenges. This study develop a versatile platform for EV N-glycoproteomic analysis (EVGpro), which enables tandem EV capture, EV protein digestion, and enrichment of N-glycopeptides. Functionalized magnetic nanochains with cell-penetrating peptides (octa-arginine, R8) enable efficient EV isolation, followed by on-chain hydrolysis to expose PEG2000 for ultrasensitive glycopeptide enrichment. The streamlined EVGpro platform identified up to 17 times more EV glycoproteins than ultracentrifugation across seven biofluids, profiling 398 EV glycoproteins from just 1 μL tear. Applied to seminal plasma, EVGpro uncover disease-specific glycoprotein signatures and identified previously unreported subtypes of asthenozoospermia. This robust and scalable approach advances the sensitive detection of disease biomarkers and molecular subtypes from diverse biofluids to enable precision medicine.